If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = 3x + 7 Multiply f * x fx = 3x + 7 Reorder the terms: fx = 7 + 3x Solving fx = 7 + 3x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 7x-1 + 3 Simplifying f = 7x-1 + 3 Reorder the terms: f = 3 + 7x-1
| 3(x-2)+2(x+1)=-19 | | 5m-24=36 | | 3x+4x+(4x+24)+x=360 | | 5x+8y=480 | | 3x+10=6x-4 | | 6(x-3)-10=32 | | 4x+3(x+2)=58 | | 4x+3(x+2)=54 | | 7+m+(6m-3)= | | 15-3x-1=12 | | 7+m+9(6m-3)= | | 8x+14=8x+14 | | 8(x+14)=8x+112 | | -29=4(u-8)-7u | | 5c-15=2c+5 | | 102.569-10.478= | | 12d-40=8 | | 2x+14=-8x-18 | | 2x+14=2x-18 | | 5n+16=n-8 | | s^3-510=0 | | 0=3x+9 | | 8c-3(c+4)=43 | | (x-6)/14=(7x)/21 | | 5x-18=2x+30 | | 2x^2+3y^2=30 | | 7+18/(6-3) | | 4(t-6)+8t=6(2t+4)-12 | | 5x^2+30x+150=1220 | | 5x+15=220000 | | -30=5+5u | | (3x/7)+3=24 |